Synthesis of novel pseudo-capacitive perovskite nanostructured flowerlike KTaO3 for lithium ion storage. (10th August 2021) - Sumedha, H.N.; Shashank, M.; Alharthi, Fahad A.; Santosh, Mysore Sridhar; Praveen, B.M.; Nagaraju, G.
Abstract: Research and technology development of lithium ion battery is very important nowadays because of its high energy and power density, low self discharge, no/less memory effect, comparatively high current output. It has been largely used in various fields like hybrid electric vehicles (EV's), portable devices, digital cameras and many more. As per our knowledge this is the first report on the synthesis of KTaO3 and examination of electrochemical performance on lithium ion batteries (LIB). The flower like nanostructured KTaO3 exhibits high interfacial area and less path length for charge transfer, which was the main reason to exhibit good electrochemical properties. The average crystallite size of material was confirmed by XRD analysis and found to be ~26 nm. The high irreversible capacity was recorded at 1307 mAh g −1 with high Columbic efficiency (~99%) at potential window of 0.01–3.00 V. Moreover, reversible first discharge capacity was measured at 432 mAh g −1 at 0.1 C current rates with exemplary cyclic stability. The capacity fade was negligible for consecutive cycles. Even at very high current rate (3C) also it presents good capacity of 74 m Ahg −1 with excellent reversibility. In addition, electrochemical impedance spectra prove the less conductive resistance at higher frequency region. Finally the present work explains the excellent electrochemical performance of nanostructured flower like KTaO3 for Li-ion battery as anode material. Graphical abstract: Image 1 Highlights: This study reports the electrochemical applications of KTaO3 flowerlike NPs as a novel anode material for LIBs. KTaO3 flower like NP was synthesised by solution combustion method by using novel fuel areca seed powder. It manifested very high irreversible discharge capacity of 1307 mAhg −1 . Excellent Columbic efficiency (~99%) was maintained throughout 200 cycles. The material shows impressive capacity (74 mAhg −1 ) even at very high current rates (3C).